A systematic surveillance programme for infectious salmon anaemia virus supports its absence in the Pacific Northwest of the United States. Issue 2 (21st November 2017) - Gustafson, L L; Creekmore, L H; Snekvik, K R; Ferguson, J A; Warg, J V; Blair, M; Meyers, T R; Stewart, B; Warheit, K I; Kerwin, J; Goodwin, A E; Rhodes, L D; et al.
Abstract: In response to reported findings of infectious salmon anaemia virus (ISAV) in British Columbia (BC), Canada, in 2011, U.S. national, state and tribal fisheries managers and fish health specialists developed and implemented a collaborative ISAV surveillance plan for the Pacific Northwest region of the United States. Accordingly, over a 3‐1/2‐year period, 4, 962 salmonids were sampled and successfully tested by real‐time reverse‐transcription PCR. The sample set included multiple tissues from free‐ranging Pacific salmonids from coastal regions of Alaska and Washington and farmed Atlantic salmon ( Salmo salar L.) from Washington, all representing fish exposed to marine environments. The survey design targeted physiologically compromised or moribund animals more vulnerable to infection as well as species considered susceptible to ISAV. Samples were handled with a documented chain of custody and testing protocols, and criteria for interpretation of test results were defined in advance. All 4, 962 completed tests were negative for ISAV RNA. Results of this surveillance effort provide sound evidence to support the absence of ISAV in represented populations of free‐ranging and marine‐farmed salmonids on the northwest coast of the United States.